A School for Parents: An Innovation in an Elementary School - Nash, Edna M. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper describes the preparation, planning and operation of a parent education project in an elementary school in British Columbia based on Adlerian theory and practice. Initiated by a joint committee of teachers and parents, between 50 and 60 parents attended each of the 21 sessions held from September to May. Sessions were comprised of leadership training, "open-centre" family counselling, parent-led small groups and recorded feedback. Progress is noted for each section as well as the teacher supervised playroom. Reported benefits to the school and families support the appropriateness of school based parent education and the need for trained counsellors to facilitate it.